2021
DOI: 10.1097/brs.0000000000003980
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Symptomatic Pseudarthrosis Observed at 1 Year After Lateral Lumbar Interbody Fusion

Abstract: Study Design. Retrospective cohort study.Objective. The aim of this study was to investigate the prognosis of symptomatic pseudarthrosis observed at 1 year after lateral lumbar interbody fusion (LLIF) surgery and to analyze the risk factors for persistent pseudarthrosis for 2 years postoperatively. Summary of Background Data. Few articles have evaluated the prognosis of symptomatic pseudarthrosis following LLIF surgery. Methods. One hundred fifty-two patients with a minimum follow-up of 2 years were screened. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…These authors also described multiple-level LLIFs, diabetes and smoking status as independent risk factors for pseudoarthrosis development. 41 Five patients in the pseudoarthrosis group had posterolateral fusion despite the features of pseudoarthrosis at the interbody fusion level. This finding might explain the asymptomatic status of these patients and underlines the importance of meticulous PLF to supplement anterior interbody fusion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These authors also described multiple-level LLIFs, diabetes and smoking status as independent risk factors for pseudoarthrosis development. 41 Five patients in the pseudoarthrosis group had posterolateral fusion despite the features of pseudoarthrosis at the interbody fusion level. This finding might explain the asymptomatic status of these patients and underlines the importance of meticulous PLF to supplement anterior interbody fusion.…”
Section: Discussionmentioning
confidence: 95%
“…The mean follow-up duration for both study groups is over 4 years and the length of follow-up is reasonable to detect most of the pseudarthroses, although seven years of follow-up has been recommended in literature. 41 Nevertheless, 8 patients (4.4%) with asymptomatic pseudoarthroses could become symptomatic in the longer term or these unfused segments with the potential fibrous union and radiologically demonstrable pseudoarthrosis could subsequently ossify into a stiff segment. A similar observation was made by Jung et al 41 in their study of 152 patients treated with single or two-level LLIF which reported a pseudarthrosis rate of 27.6% (42/152) at 1-year follow-up, which decreased to 12.5% (19/152) at 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLIF procedure was performed as previously described 27–29 . A PEEK cage filled with cancellous allograft bone chips mixed with bone marrow was inserted in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…The LLIF procedure was performed as previously described. [27][28][29] A PEEK cage filled with cancellous allograft bone chips mixed with bone marrow was inserted in all patients. After wound closure, the patient was repositioned prone for posterior fixation.…”
Section: Surgical Techniquementioning
confidence: 99%